Electrocardiogram as a predictor of survival without appropriate shocks in primary prophylactic ICD patients: A retrospective multi-center study. (15th June 2020) - Pelli, Ari; Kenttä, Tuomas V.; Junttila, M. Juhani; Bergau, Leonard; Zabel, Markus; Malik, Marek; Reichlin, Tobias; Willems, Rik; Vos, Marc A.; Harden, Markus; Friede, Tim; Sticherling, Christian; et al.
Abstract: Background: Abnormal 12-lead electrocardiogram (ECG) can predict cardiovascular events, including sudden cardiac death. We tested the hypothesis that ECG provides useful information on guiding implantable cardioverter defibrillator (ICD) therapy into individuals with impaired left ventricular ejection fraction (LVEF). Methods: Retrospective data of primary prevention ICD implantations from 14 European centers were gathered. The registry included 5111 subjects of whom 1687 patients had an interpretable pre-implantation ECG available (80.0% male, 63.3 ± 11.4 years). Primary outcome was survival without appropriate ICD shocks or heart transplantation. A low-risk ECG was defined as a combination of ECG variables that were associated with the primary outcome. Results: A total of 1224 (72.6%) patients survived the follow-up (2.9 ± 1.7 years) without an ICD shock, 224 (13.3%) received an appropriate shock and 260 (15.4%) died. Low-risk ECG defined as QRS duration <120 ms, QTc interval <450 ms for men and <470 ms for women, and sinus rhythm, were met by 515 patients (30.5%). Multivariable Cox regression showed that the hazard (HR) for death, heart transplantation or appropriate shock were reduced by 42.5% in the low-risk group (HR 0.575; 95% CI 0.45–0.74; p < 0.001), compared to the high-risk group. The HR for the first appropriate shock was 42.1% lower (HR 0.58; 95% CI 0.41–0.82; p = 0.002) and the HR for death was 48.0% lower (HR 0.52; 95% CI 0.386–0.72; p < 0.001) in the low-risk group. Conclusion: Sinus rhythm, QRS <120 ms and normal QTc in standard 12-lead ECG provides information about survival without appropriate ICD shocks and might improve patient selection for primary prevention ICD therapy. Highlights: 12-lead ECG identifies the patients who may not benefit from primary prophylactic ICD patients. Low risk ECG is defined as QRS duration <120 ms, sinus rhythm, and normal QTc duration. 12-lead ECG can be used together with other risk variables in identifying the candidate for prophylactic ICD therapy.